The Land of Prehistory: A Critical History of American Archaeology. Alice Beck Kehoe. Routledge. New York - David L. Browman (Bulletin of the History of Archaeology, 1999)
This book is a very difficult work to read dispassionately, for a variety of reasons, such as difficulties the reader may have with a rather convoluted discussion of Daniel Wilson and the Scottish enlightenment, the categorization of many practicing archaeologists as "petrified puddle ducks", after a term borrowed from Waiter Taylor. and taking a leaf from Taylor, utilization of the term "critical" primarily as "criticism", so that almost no current significant practicing archaeologist in North America comes out unscathed. The term puddle ducks" was employed in several places. Perhaps the strongest usage when Kehoe states (p. 183) that "Compared to the political sophistication displayed by so many social anthropologists, mainstream American archaeologists have been petrified puddle ducks." The term "petrified puddle ducks" had a nice ring to it but I confess I did not remember the context that Taylor employed it in, so I repaired to the volume to re-educate myself.